Systematic Literature Review: Problem Based Learning Berbantuan PhET terhadap Berpikir Kritis Siswa SMA Fisika - Sari, Santi Kencana; Nugroho, Sunyoto Eko; Subali, Bambang (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Critical thinking is an essential competency in 21st-century physics learning because many physics concepts are abstract and require analytical as well as problem-solving abilities. The integration of Problem Based Learning (PBL) with PhET simulations is considered to support the development of these skills. This study aims to systematically analyse research trends on the implementation of PBL assisted by PhET simulations in improving senior high school students’ critical thinking skills in physics learning. The study employed a Systematic Literature Review (SLR) following PRISMA guidelines and was combined with bibliometric analysis using VOSviewer. Articles were identified through Google Scholar using Publish or Perish within the 2020–2026 publication period, producing 994 records at the identification stage. After the screening, eligibility, and inclusion processes, 64 articles met the inclusion criteria and were analysed. The findings indicate that publication trends rose during 2023–2024, the keywords Problem Based Learning, PhET simulation, critical thinking, and physics learning were strongly interconnected across four bibliometric clusters, and the most frequently studied physics topics were oscillation and waves, dynamic electricity, and motion with Newtonian concepts. Overall, the reviewed studies show a positive tendency of PBL assisted by PhET simulations in supporting students’ critical thinking skills.